Synthesis of BiNbO4 by the Flux Method. (26th September 2012) - Maruyama, Yuki; Izawa, Chihiro; Watanabe, Tomoaki
Abstract : BiNbO 4 has been successfully synthesized using Bi2 O3 –B2 O3 eutectic flux. In particular, we succeeded in synthesizing a low-temperature-phase BiNbO 4 crystal ( α -BiNbO 4 ) at 1073 K as well as high-temperature-phase BiNbO 4 crystal ( β -BiNbO 4 ). The morphology of α -BiNbO 4 and β -BiNbO 4 particles prepared by the flux method is a euhedral crystal. In contrast, the morphology of particles prepared by solid state reaction differs: α -BiNbO 4 is aggregated and β -BiNbO 4 is necked. Ultraviolet-visible diffuse reflectance spectra indicate that the absorption edge is at a longer wavelength for β -BiNbO 4 than for α -BiNbO 4 with β -BiNbO 4 absorbing light of wavelengths up to nearly 400 nm.